Research on carbon emission accounting model for open-pit mines in alpine ecologically fragile areas - Guoqing LI; Bin BAI; Guiqi LI; Kai GUAN; Jie HOU; Chunping LIN (工程科学学报)
To accurately measure carbon emissions from open-pit mines in alpine ecologically fragile areas, a rigorous and comprehensive accounting method is essential. This method must account for both direct emissions from mining operations and indirect emissions from ecological disturbances. The unique challenges of high-altitude environments require a sophisticated carbon accounting approach that tracks emissions from both mining activities and their broader ecological impacts on carbon sinks and sources. This study begins by examining the carbon cycle mechanisms unique to open-pit mines in these fragile regions, characterized by high altitudes, low temperatures, and delicate ecosystems susceptible to disturbances. Leveraging life cycle theory, we define the accounting boundaries to encompass all stages of the mining life cycle, namely extraction, transportation, beneficiation, and auxiliary processes. A key aspect of this research is the meticulous examination of direct and indirect carbon emissions across various mining stages. The energy-intensive nature of mining, along with the substantial transportation requirements over challenging terrains, significantly contributes to the carbon footprint. Additionally, beneficiation processes involving the separation and refinement of raw materials are highly energy-consuming, increasing indirect emissions. By mapping these processes and analyzing their carbon emission contributions, we enhance the understanding of the carbon cycle’s impact owing to high-altitude mining. The study also elucidates the structure of carbon sources and sinks within these fragile ecosystems. We compile a detailed carbon emission source inventory for open-pit mines, providing a comprehensive reference for emission sources and natural carbon sinks, such as soil and vegetation, potentially compromised by mining activities. This inventory is instrumental in developing a more precise accounting model. We have developed a carbon emission accounting model that integrates mining production stages with changes in carbon sinks owing to mining-induced disturbances. This model specifically accounts for the increased energy consumption of mining equipment at high altitudes, leading to higher carbon emissions owing to reduced operational efficiency. The model offers a nuanced estimate of total emissions by incorporating these factors. The model was validated using a case study of an open-pit metal mine in Tibet, a region renowned for its alpine ecology and environmental fragility. Applying the model revealed total carbon emissions of 1.76295×105 t CO2 for 2023, reflecting the combined direct and indirect impacts of mining on the ecosystem. This case study demonstrates the model’s effectiveness and underscores the considerable carbon footprint of mining in alpine regions. This research provides a theoretical foundation for carbon emission accounting and management in high-altitude, ecologically sensitive mining areas. It presents a detailed and scientifically rigorous accounting method supporting sustainable mining practices. The findings and model offer practical insights for industry stakeholders and a data-driven framework for policymakers aiming to reduce the environmental footprint of mining in vulnerable ecosystems. This study paves the way for sustainable resource extraction in ecologically sensitive zones, supporting efforts to minimize the carbon footprint of mining operations in high altitudes.